(untitled) (Research, Society and Development, 2021)
The Acquired immunodeficiency syndrome - AIDS is the most advanced stage of the contagious complex of human immunodeficiency virus - HIV infection. In Brazil, approximately 40 thousand new AIDS cases have appeared in the last five years. Among the main groups affected are women sex workers - MPS. Based on this fact, this study aimed to present the collective discourse of the MPS on condom use and their self-perception of vulnerability against of HIV infection. This is a descriptive, cross-sectional, analytical, qualitative study, carried out with MPS in Floriano, Piauí State. Data collection took place between the months of September 2019 and March 2020. The collective subject discourse method - DSC proposed by Fiorin guided the analysis of the participants’ testimonies. All MPS (n = 5) reported knowing the need to use condoms to minimize vulnerability to HIV during all sexual relations. For them, the use of condoms is an essential method to prevent health during sexual intercourse. 80.0% (n = 4) of the participating women reported not feeling vulnerable to HIV. When investigating the perceptions of MPS about condom use by them during sex, good acceptance was identified among them. for them, the use of condoms is a health issue and is above the opportunity to earn money.